MEDIA EXPOSURE, KNOWLEDGE AND ATTITUDE TOWARDS THAILAND 4.0 OF PEOPLE IN BANGKOK - Songsiri, Awinda (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2021)
The objective of this research was to study 1) media exposure, knowledge, and attitude towards Thailand 4.0; 2) the exposure to news about Thailand 4.0 among different demographic characteristics; and 3) the relationship between exposure to news, knowledge, and attitude about Thailand 4.0. Quantitative research was done with data collected by questionnaire from 400 samples, all Bangkok Metropolitan Area (BMA) residents aged 15 and over. Data was analyzed by frequency, mean, percentage, standard deviation, t-test, one-way analysis of variance (ANOVA), and the Pearson product-moment correlation coefficient with correlations among study variables. Results were that frequency of exposure to news about Thailand 4.0 from different general media was moderate and frequency of media exposure through social networks (Facebook/Twitter) was higher than other media. Knowledge of Thailand 4.0 was moderate, with the most knowledge about applying modern agricultural technology to solve farming problems. Overall attitude about Thailand 4.0 was positive attitude level. Age, educational level and average monthly income influenced exposure frequency to media, but there was a low correlation between exposure frequency to different media news and knowledge of Thailand 4.0 (r = 0.154) and low positive correlation of attitudes about Thailand 4.0 (r = 0.269). In terms of knowledge, there was a moderate positive relationship between attitude about Thailand 4.0 (r = 0.427) at a statistical significance of 0.05.